A pharmacokinetic evaluation of alpelisib for the treatment of HR+, HER2-negative, PIK3CA-mutated advanced or metastatic breast cancer. (1st February 2021) - Bertho, Marion; Patsouris, Anne; Augereau, Paule; Robert, Marie; Frenel, Jean-Sebastien; Blonz, Cyriac; Campone, Mario
ABSTRACT: Introduction : In most cases, metastatic breast cancer remains an incurable disease. A PIK3CA mutation is detected in 30–40% of all hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2–) advanced breast cancers. PIK3CA activating mutations have been linked to endocrine resistance. PI3K inhibitors therefore offer promising new therapeutic options for this disease. Areas covered : This review discusses the pharmacologic properties, preclinical development, clinical efficacy, and safety profile of alpelisib, a PI3K inhibitor indicated in HR+/HER2 – PIK3CA-mutated advanced breast cancer, describing current therapeutic indication and open questions. Expert opinion : Following results of the SOLAR-1 trial, alpelisib became the first PI3K inhibitor approved by the U.S. Food and Drug Administration, in combination with fulvestrant, for postmenopausal women and men with HR+/HER2 – PIK3CA-mutated advanced breast cancer following progression on or after an endocrine-based regimen. This trial showed a substantial improvement in progression-free survival. However, given the side effects of alpelisib, the treatment decision should follow a thorough benefit-risk assessment. The BYLieve trial suggests alpelisib-fulvestrant benefit after progression on CDK 4/6 inhibitors. The identification of patients that are likely to benefit the most from PI3K inhibitors is still eagerly sought.